Genome-wide identification of calcineurin B-like protein-interacting protein kinase gene family reveals members participating in abiotic stress in the ornamental woody plant Lagerstroemia indica - Yu, Chunmei; Ke, Yongchao; Qin, Jin; Huang, Yunpeng; Zhao, Yanchun; Liu, Yu; Wei, Hui; Liu, Guoyuan; Lian, Bolin; Chen, Yanhong; Zhong, Fei; Zhang, Jian (Frontiers in Plant Science, 2022)
CBL-interacting protein kinases (CIPKs) play important roles in plant responses to stress. However, their function in the ornamental woody plant Lagerstroemia indicais remains unclear. In this study, the LiCIPK gene family was analyzed at the whole genome level. A total of 37 LiCIPKs, distributed across 17 chromosomes, were identified. Conserved motif analysis indicated that all LiCIPKs possess a protein kinase motif (S_TKc) and C-terminal regulatory motif (NAF), while seven LiCIPKs lack a protein phosphatase interaction (PPI) motif. 3D structure analysis further revealed that the N-terminal and C-terminal 3D-structure of 27 members are situated near to each other, while 4 members have a looser structure, and 6 members lack intact structures. The intra- and interspecies collinearity analysis, synonymous substitution rate (Ks) peaks of duplicated LiCIPKs, revealed that ~80% of LiCIPKs were retained by the two whole genome duplication events that occurred approximately 56.12–61.16 million year ago (MYA) and 16.24-26.34 MYA ago. The promoter of each LiCIPK contains a number of auxin, abscisic acid, gibberellic acid, salicylic acid, and drought, anaerobic, defense, stress, and wound responsive cis-elements. Of the 21 members that were successfully amplified by qPCR, 18 LiCIPKs exhibited different expression patterns under NaCl, mannitol, PEG8000, and ABA treatments. Given that LiCIPK30, the AtSOS2 ortholog, responded to all four types of stress it was selected for functional verification. LiCIPK30 complements the atsos2 phenotype in vivo. 35S:LiCIPK-overexpressing lines exhibit increased leaf area increment, chlorophyll a and b content, reactive oxygen species scavenging enzyme activity, and expression of ABF3 and RD22, while the degree of membrane lipid oxidation decreases under NaCl treatment compared to WT. The evolutionary history, and potential mechanism by which LiCIPK30 may regulate plant tolerance to salt stress were also discussed. In summary, we identified LiCIPK members involved in abiotic stress and found that LiCIPK30 transgenic Arabidopsis exhibits more salt and osmotic stress tolerance than WT. This research provides a theoretical foundation for further investigation into the function of LiCIPKs, and for mining gene resources to facilitate the cultivation and breeding of new L. indica varieties in coastal saline-alkali soil.